Willingness of Older Adults From Culturally Diverse Populations to Participate in COVID-19 Related Treatment Trials and Associated Factors - Ellen Leslie Brown EdD, MS, RN, FAAN; Amy Paul-Ward PhD; Donna Felber Neff PhD, RN, FNAP; Fern J. Webb PhD; Edgar Ramos Vieira PT, MSc, PhD; Trudy Gaillard PhD, RN, CDCES, FAHA (Gerontology and Geriatric Medicine, 2023)
This survey study aimed to assess the willingness of culturally diverse older adults to participate in COVID-19 research. The majority of the 276 participants were women (81%, n  = 223) and Black/African American (62%, n  = 172) or White Hispanic (20%, n  = 56). A key finding from the survey was less than 1 of 10 respondents would be likely to participate in COVID-19 related research if given the opportunity. There were no differences observed by gender, race or ethnicity. Implications of these findings are considered. These study findings indicate continued effort and better messaging strategies are required to increase awareness that COVID-19 related research needs to include culturally diverse older adults to ensure vaccines and treatments are efficacious in different populations.